Reactive oxygen species at the crossroads of inflammasome and inflammation - Harijith, Anantha; Ebenezer, David L.; Natarajan, Viswanathan (Frontiers in Physiology, 2014)
Inflammasomes form a crucial part of the innate immune system. These are multi-protein oligomer platforms that are composed of intracellular sensors which are coupled with caspase and interleukin activating systems. Nod-like receptor protein (NLRP) 3, and 6 and NLRC4 and AIM2 are the prominent members of the inflammasome family. Inflammasome activation leads to pyroptosis, a process of programmed cell death distinct from apoptosis through activation of Caspase and further downstream targets such as IL-1β and IL-18 leading to activation of inflammatory cascade. Reactive oxygen species (ROS) serve as important inflammasome activating signals. ROS activate inflammasome through mitogen-activated protein kinases (MAPK) and extracellular signal-regulated protein kinases 1 and 2 (ERK1/2). Dysregulation of inflammasome is plays a significant role in various pathological process. Viral infections such as Dengue and Respiratory syncytial virus activate inflammasomes. Crystal compounds in silicosis and gout also activate ROS. In diabetes, inhibition of autophagy with resultant accumulation of dysfunctional mitochondria leads to enhanced ROS production activating inflammasomes. Activation of inflammasomes can be dampened by antioxidants such as SIRT-1. Inflammasome and related cascade could serve as future therapeutic targets for various pathological conditions.